The continuity of the prevention of smallpox in Peru: measures of the Superior Government (1806-1820) to the Government of the Protectorate (1822) (Revista revoluciones, 2021)
The present research was carried out between the months of April and May of the year 2020, during the Quarantine ordered by the Peruvian State by the Pandemic of the COVID-19, therefore, it was only carried out with the books of the personal library of the author and in this work we present a study of the Impact of smallpox in the different European Royal Houses and how King Carlos IV of Spain sought to prevent this disease to through the vaccine, both in the Metropolis and in its domains of America, including the Peruvian Viceroyalty. The continuity of the Bourbon Policy will be seen in the Normativity of the 1st Independent State: The Protectorate (1821 – 1822).
Keywords: History of medicine; epidemics; Protectorate; Royal Houses